A universidade mercantil e o caso da universidade pública: reflexões a partir da experiência chilena - Adolfo Ignacio Calderón (EccoS – Revista Científica)
In this article, we discuss about the collapse of the Brazilian Public Universities, as an hegemonical universitary model. Taking into the account the Chilean case, we hypothetically analyse the diversification consequences of the financial sources, the main and the most polemical propose to overcome the financing crisis of the state universities, widely recommended by the World Bank and delimitted in the State fiscal crisis. In this context, the author points out the emergency of a mercantile university, a new university pattern and not a simple adjective created to name, in a biased way, any private system university. This new university model would be the base, the matrix above what all the universitary system would build up. After such model, each university will have its specific talent, and could do whatever wish with the profits or the surplus, as well. It is a kind of pattern which will allow the universities to act without limitations or strait-jacket in answering the market demand